1967
DOI: 10.1037/h0025049
|View full text |Cite
|
Sign up to set email alerts
|

Delay of positive reinforcement in instrumental eyelid conditioning.

Abstract: Effects of delay of instrumental reinforcement on human eyelid conditioning were investigated in 5 groups of 20 Ss each with delays of 0, 0.5, 1.0, 2.0, and 4.0 sec. between response and reinforcement. The reinforcement was illumination of a small lamp and operation of an electric counter, and S was told only that if he did the right thing the reinforcement would occur. Acquisition appeared to be maximal when the reinforcement was delayed from .5 to 2.0 sec. The function was a flat-topped inverted U with 0 del… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
12
1

Year Published

1968
1968
2016
2016

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 6 publications
(15 citation statements)
references
References 13 publications
2
12
1
Order By: Relevance
“…In a social analog of instrumental reward conditioning, employing five levels of delay, Weiss (1967) found negatively accelerated decreasing delay gradients for both response speed and response probability measures. Cerekwicki and Grant (1967) in a study involving five levels of delay found an inverted-U-shaped gradient of eyelid response probablity, and they were careful to demonstrate that this surprising finding was replicable (Cerekwicki, Kantowitz, & Grant, 1969). The results of the present study and other recent studies serve to deepen the mystery of the Cerekwicki and Grant results, particularly where closely comparable time intervals were employed (Karras, 1967), while providing instances of monotonic decreasing gradients in a variety of human conditioning situations.…”
Section: Discussionsupporting
confidence: 65%
“…In a social analog of instrumental reward conditioning, employing five levels of delay, Weiss (1967) found negatively accelerated decreasing delay gradients for both response speed and response probability measures. Cerekwicki and Grant (1967) in a study involving five levels of delay found an inverted-U-shaped gradient of eyelid response probablity, and they were careful to demonstrate that this surprising finding was replicable (Cerekwicki, Kantowitz, & Grant, 1969). The results of the present study and other recent studies serve to deepen the mystery of the Cerekwicki and Grant results, particularly where closely comparable time intervals were employed (Karras, 1967), while providing instances of monotonic decreasing gradients in a variety of human conditioning situations.…”
Section: Discussionsupporting
confidence: 65%
“…Apparatus.-The apparatus and laboratory were the same as that used by Fleming and Grant (1966) and Cerekwicki and Grant (1967). The 5 1 sat in an ophthalmological examination chair in an inner soundproofed chamber and faced a rectangular wooden enclosure painted flat white and illuminated to about 2 mL.…”
Section: Methotfmentioning
confidence: 99%
“…This result was surprising given the ease with which bobwhite chicks generally form strong preferences for the particular training stimulus used, maternal Call A (see Harshaw & Lickliter, ). Nevertheless, exceptions to strict hyperbolic discounting have been noted (e.g., Cerekwicki & Grant, ; Cerekwicki et al., ; Landauer, ), particularly for “very brief” delays of less than a second (see Schneider, ). Studies of brief unsignaled delay of reinforcement have, for example, often reported an increase in response rate with delayed compared to immediate reinforcement (Arbuckle & Lattal, ; Lattal & Ziegler, ; Richards, ; Sizemore & Lattal, ).…”
Section: Resultsmentioning
confidence: 99%
“…Although it is a truism in psychophysics and many areas of neuroscience that “timing is everything” when it comes to isolating the workings of a particular cognitive process, thinking about the effects of delay on learning in operant paradigms is dominated by the idea that the potency of reinforcers declines in a straightforward, hyperbolic fashion with increased delay (e.g., Mazur, ; Takahashi et al., ). Studies showing violations of hyperbolic decline with delays of less than one‐second have thus tended to be ignored and/or stand as unexplained anomalies in the literature (e.g., Cerekwicki et al., ; Cerekwicki & Grant, ; Landauer, ; cf. Schneider, ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation